(untitled) (Fiep Bulletin - online, 2014)
The Brazilian population, as well as the world’s population, is aging gradually, which makes the health areaprofessionals comprehension of aging and its processes increasingly necessary. Thus, this study had as objective to evaluate theknowledge degree of the Physical Therapy graduation course students about aging. For that, it was applied the Palmorequestionnaire to the last periods Physical Therapy course students in the city of Foz do Iguaçu - PR. The studied sample (n=30)presented a satisfactory index of right answers in questions concerning the physiological processes intrinsic to aging, morerelated to the Geriatrics knowledge area. On the other hand, it was observed a little satisfactory index of right answers inquestions related to the social and cultural aspects of aging, which refers to Gerontology. This made it possible to conclude thatthe knowledge about the aging biopsychosocial aspects in an integrated way is little satisfactory among the Physical Therapystudents, which does not match with the holistic approach perspective in health, being, therefore, necessary the extension of thissubject into the physical therapist graduation.